2019
DOI: 10.1111/imm.13035
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory role of acid sphingomyelinase in allergic asthma

Abstract: Acid sphingomyelinase (ASM) is one of the enzymes that catalyzes the breakdown of sphingomyelin to ceramide and phosphorylcholine. In this study, we aimed at elucidating the role of ASM in allergic asthma. We used an ovalbumin-induced murine model of asthma where we compared wild-type and ASM-deficient mice. In wild-type mice, secretory ASM activity in the bronchoalveolar lavage fluid was increased in the acute ovalbumin model, but not in a tolerogenic model. Furthermore, in the absence of ASM, the serum IgE l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
2
11
1
Order By: Relevance
“…In that study, Asm was not elevated in the control groups with asthma or adenovirus infections . This is in line with our results demonstrating that asthmatic sensitization and provocation itself does not alter Asm activity, but in contrast to the results by Sopel et al Yang et al stimulated bone marrow‐derived mast cells of WT mice in vitro with antigens, which resulted in an activation of Asm, while Asm inhibition via amitriptyline decreased antigen‐induced Ca 2+ influx and Asm activity. After induction of systemic anaphylaxis, disease activity was less pronounced in Asm −/− animals compared with WT littermates .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In that study, Asm was not elevated in the control groups with asthma or adenovirus infections . This is in line with our results demonstrating that asthmatic sensitization and provocation itself does not alter Asm activity, but in contrast to the results by Sopel et al Yang et al stimulated bone marrow‐derived mast cells of WT mice in vitro with antigens, which resulted in an activation of Asm, while Asm inhibition via amitriptyline decreased antigen‐induced Ca 2+ influx and Asm activity. After induction of systemic anaphylaxis, disease activity was less pronounced in Asm −/− animals compared with WT littermates .…”
Section: Discussionsupporting
confidence: 92%
“…In that study, Asm was not elevated in the control groups with asthma or adenovirus infections. 11 This is in line with our results demonstrating that asthmatic sensitization and provocation itself does not alter Asm activity, but in contrast to the results by Sopel et al 20 In previous studies it was demonstrated that ASM regulates pathogenic T H 1-and T H 17-differentiation and responses, while it enhances regulatory T cell development and function. 35,36 In line with our data, naïve Asm −/− mice had higher numbers of systemic T reg cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is well documented that sphingolipids play vital roles in the regulation of immune and adaptive cell senescence. For example, most sphingolipids were found to be higher in T cells from A compared to Y mice, and the addition of exogenous C2 and C6 ceramide inhibited T cell proliferation ( Kirk and Miller, 1999 ; Martinova, 1998 ; Sopel et al, 2019 ). These data are consistent with our data presented here, demonstrating that age-related ceramide increases may contribute to the proliferative and functional defects observed in aged T cells through the induction of Drp1-mediated mitochondrial fission and mitophagy.…”
Section: Discussionmentioning
confidence: 99%